The dynamic landscape of virtual space explored through a multidisciplinary kaleidoscope - REZEANU, C.-I. (Transilvania University of Brasov Publishing House, 2018)
A social life disconnected from space it`s difficult to conceive. However, in sociology, the concept of space is still underdeveloped, missing from theories, dictionaries, or encyclopaedias. For more than a century, sociologists have assumed space as a passive scene for social actions, and implied as material, static, continuous and linearly travelled. In the new context of information society, economic globalisation, and postmodern hyper-reality, scholars question the conventional definitions of space. We believe sociologists will arrive at a more nuanced understanding of space, by taking an interdisciplinary approach, and focusing on how space is lived. We use virtual space as a proxy for understanding how complex space can be, and frame it through the concept of “cultural landscape” to capture its relational, dynamic, and socially constructed dimensions. Our aim is to illustrate the dynamism, versatility, and fluidity of virtual space by moving from one discipline and theoretical perspective to the other and interpreting the newly configured landscapes. We show that virtual space is a discontinuous imaginary process, organised in networks with multiple layers, experienced as a journey into a narrative text or as a ”consensual hallucination”, where the evanescence of the body and the anonymity of the self boost the quest for authenticity, self-discovery, self-disclosure and intimacy. Nonetheless, virtual space, due to its potential to equalise statuses, minimise authority and multiply the audiences of messages, is becoming the enabler of Habermasian communicative rationality, rousing moral consciousness and triggering civic actions.